Analisis Keterampilan Sosial Peserta Didik pada Mata Pelajaran IPS Kelas VIII - Hidayat, Adin; Aminuyati, Aminuyati; Okianna, Okianna; Buwono, Sri; Barella, Yusawinur (Indo-MathEdu Intellectuals Journal, 2023)
This research aimed to determine the social skills of students in the subject of Social Science in the eighth grade at SMP Negeri 09 Teluk Keramat, focusing on aspects of communication and cooperation abilities. The study utilized a descriptive method with a qualitative design. The participants in this study were teachers who teach social science and eighth-grade students. Data collection techniques include observation, interviews, and documentation. The data collection tools were observation guidelines, interview guidelines, and documentation tools. Data analysis technique involve data reduction, data presentation, and drawing conclusions. The validation of the data is carried out using triangulation techniques. The results of this research indicate: (1) the social communication skills of students in learning social science are not yet optimal. This is because students feel hesitant when speaking to convey opinions or ask questions, and often use the local language when communicating in the classroom; (2) the social cooperation skills of students in learning social science are already good. This is evidenced students who can assist their peers in explaining group discussion tasks, refrain from blaming their peers' opinions, actively listen when their peers express their opinions, and take responsibility for completing the group discussion assign.